Assessment of the impact of a newly introduced free-ranging group of chimpanzees (Pan troglodytes schweinfurthii) on the vegetation of Ngamba Island, Lake Victoria in Uganda - Van Rooyen, M.W. (Margaretha W.), 1950- (University of Pretoria, 2013)
Dissertation (MSc(Wild Life Management))--University of Pretoria, 2006.